To simplify this expression you just need to modify one of the terms so it has the same power of ten as the other. I find it easier to lower a power than raise it so we'll use the fact that \(\displaystyle{10}^{{{11}}}={100}×{10}^{{{9}}}.\) Then

\(\displaystyle{9.5}×{\left({10}^{{{11}}}\right)}+{6.3}×{10}^{{{9}}}={9.5}×{100}×{\left({10}^{{{9}}}\right)}+{6.3}×{10}^{{{9}}}={950}×{\left({10}^{{{9}}}\right)}+{6.3}×{10}^{{{9}}}={\left({950}+{6.3}\right)}×{10}^{{{9}}}={956.3}×{10}^{{{9}}}\)

Note that if your course has recently covered maintaining significant figures, then you'll need to round this to the tens place. Hence your answer will instead be \(\displaystyle{950}×{10}^{{{9}}}={9.5}×{10}^{{{11}}}\)

\(\displaystyle{9.5}×{\left({10}^{{{11}}}\right)}+{6.3}×{10}^{{{9}}}={9.5}×{100}×{\left({10}^{{{9}}}\right)}+{6.3}×{10}^{{{9}}}={950}×{\left({10}^{{{9}}}\right)}+{6.3}×{10}^{{{9}}}={\left({950}+{6.3}\right)}×{10}^{{{9}}}={956.3}×{10}^{{{9}}}\)

Note that if your course has recently covered maintaining significant figures, then you'll need to round this to the tens place. Hence your answer will instead be \(\displaystyle{950}×{10}^{{{9}}}={9.5}×{10}^{{{11}}}\)